The Influence Of Work Motivation And Work Discipline On Employee Performance At The DPRD Secretariat Of North Sumatra Province - Bulan Febrian; Desi Astuti (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to determine the effect of work motivation on employee performance at the Secretariat Office of the DPRD of North Sumatra Province. The approach method used is quantitative with a quantitative descriptive research type in the form of numbers and statistical analysis. This type of research is associative. The population in this study were all employees at the Secretariat of the DPRD of North Sumatra Province, totaling 132 people. Sampling in this study used a probability sampling technique, namely proportionate stratified random sampling using the Slovin formula, the sample in this study was 57 people. The data collection technique used was through a questionnaire. The data analysis technique in this study used multiple regression, classical assumption testing, and hypothesis testing. . Based on the results of this study, the significance value of work motivation on performance based on the t test was obtained at t count> t table (3.857> 2.001). Thus Ho is rejected. The conclusion: work motivation has a positive and significant effect on performance in the DPRD of North Sumatra Province. Based on the results of this study, the significance value of work discipline based on the t test was obtained at t count> t table (4.912> 2.001). Thus H1 is accepted. The conclusion: work discipline has a positive and significant effect on employee performance in the DPRD of North Sumatra Province. Based on the results of the F test above, the value of F count> F table was obtained at (25.636> 3.16) (Sig. 0.000 <α0.05), thus H0 is rejected. The conclusion: work motivation, work discipline has a positive and significant effect on employee performance in the DPRD of North Sumatra Province.